Measuring absenteeism as a precondition of quality management of absenteeism - Ilić Đurđijana (Trendovi u Poslovanju)
Absenteeism in the workplace is an infrequent phenomenon that is given little importance. Frequent absences of workers from work processes have a detrimental effect on costs as well as on the overall productivity of the business system, which ultimately results in the competitiveness of the end product or service. In most cases, the employer only sees the direct costs of absenteeism (for example sickness benefit), while the other (indirect) costs are not usually taken into account by the employer. Indirect costs such as the cost of a replacement worker (education, managerial hours due to additional supervision), administrative costs and costs associated with a decline in productivity are very difficult to grasp without specialized knowledge and skills. Therefore, employers generally declare the costs of absenteeism immeasurable, minor and difficult to manage without affecting the organization and cost of labor. Previous models of absenteeism control have mostly been of a repressive nature and most often have had a negative impact on the organizational culture and reputation of the employer in the context of corporate social responsibility. By repressive control, absences at first seem to shrink, while real costs increase rapidly, and organizational culture, at the same time, deteriorates. In order to counteract the above, it is recommended to introduce such measures and activities that result in significant financial savings while increasing employee satisfaction and improving the overall efficiency of the organization.